EL ENFOQUE INTERDISCIPLINARIO DE LOS CONTENIDOS COMO VÍA PARA LOGRAR UN PROCESO ENSEÑANZA-APRENDIZAJE MÁS EFECTIVO EN LA ESCUELA MULTÍGRADO: INTERDISCIPLINARY APPROACH FOR THE CONTENTS AS A WAY TO FULFILL A MORE EFFECTIVE TEACHING-LEARNING PROCESS IN THE MULTI-GRADE SCHOOL - Comendador Laguna, Juana; Escobedo González, Oralia; Martínez Sánchez, Natacha (Opuntia Brava, 2018)
El trabajo hace referencia a un sistema de ejercicios y al procedimiento para su elaboración, de acuerdo con los dos momentos de desarrollo de los niños en etapa escolar que estudian en escuelas multígrados, estos son: 1ro-2do y 3ro-4to. Esta propuesta facilita el aprendizaje más efectivo de los contenidos de la asignatura “El mundo en que vivimos”, y favorece la actividad independiente, la socialización del proceso, la sistematización de los conocimientos, y la atención a la diversidad en las aulas multígrados. ABSTRACT This work makes reference to a system of exercises and to the procedure for its elaboration, in accordance to two moments of the children development period who study al multi-grade schools; they are 1st-2nd and 3rd-4th. This proposal eases the learning of the content of the subject “The world we are living in” and it favors the independent activity, the process of socializing, the systematization of knowledge, and the attention to diversity in multi-grade classrooms. KEY WORDS: learning, interdisciplinary, multi-grade school, procedure.